Balancing Shareability and Positive Interdependence to Support Collaborative Problem-Solving on Interactive Tabletops. (24th April 2021) - Maquil, Valérie; Afkari, Hoorieh; Arend, Béatrice; Heuser, Svenja; Sunnen, Patrick
Abstract : To support collaboration, researchers from different fields have proposed the design principles of shareability (engaging users in shared interactions around the same content) and positive interdependence (distributing roles and information to make users dependent on each other). While, on its own, each principle was shown to successfully support collaboration in different contexts, these principles are also partially conflicting, and their combination creates several design challenges. This paper describes how shareability and positive interdependency were jointly implemented in an interactive tabletop-mediated environment called Orbitia, with the aim of inducing collaboration between three adult participants. We present the design details and rationale behind the proposed application. Furthermore, we describe the results of an empirical evaluation focusing on joint problem-solving efficiency, collaboration styles, participation equity, and perceived collaboration effectiveness.